Penegakan Hukum Terhadap Pelaku Pencemaran Lingkungan Terkait Sampah Elektronik di Sidoarjo - Rahmawati, Yuli; Rosnawati, Emy (Wadah Inovasi Indonesia, 2024)
This research uses sociological juridical with an empirical approach. Primary data used is Law Number 32 of 2009 concerning Environmental Protection and Management. Meanwhile, secondary data is in the form of statutory regulations, books, and journals relating to environmental criminal law enforcement related to environmental pollution due to electronic waste. The legal material analysis technique used is deductive. To obtain data that matches the facts in the field, this research was located at the Sidoarjo Regency Environment and Hygiene Service. The results of this research found that government officials as providers of authority or permits regarding the environment, especially electronic waste, only carried out outreach. Administrative law enforcement carried out by the Sidoarjo Regency Environment and Hygiene Service is still not running optimally and only has the authority to issue permits for B3 waste collection on a district scale. Then, the public as law enforcers tend to be indifferent, such as the lack of level of compliance in complying with provisions related to the obligation to carry out electronic waste management.